Sustainability and Social Interest Housing - Grzegowski, Flávia Costa; Diniz, Luciana Nemer (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
The article describes the concepts of sustainability in a historical view of the subject. The text assesses the evolution of the Minha Casa Minha Vida program (MCMV) and its relevant production for Social Interest Housing (HIS) in Brazil in this century. The research also lists the impacts of sustainable practices applied to that program. In the methodology, consultations in secondary sources (books, articles and theses) and the research of documents from the state, municipal and federal spheres stand out. This analysis of these documents is responsible for a more precise investigation on the subject. The conclusions highlight how the concept of sustainability applied to housing programs can generate increasingly higher standards of housing, suitable for the target audience.